2005
DOI: 10.1209/epl/i2005-10024-4
|View full text |Cite
|
Sign up to set email alerts
|

An experimental test of the Jarzynski equality in a mechanical experiment

Abstract: We have experimentally checked the Jarzynski equality and the Crooks relation (see Jarzynski C.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
233
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(240 citation statements)
references
References 16 publications
3
233
0
3
Order By: Relevance
“…Eq. 1 and closely related results [5,6,7], along with experimental confirmations [8,9,10,11], have revealed that equilibrium free energy differences can be determined from distributions of nonequilibrium work values. The recent progress in this area has drawn attention to a set of earlier papers by Bochkov and Kuzovlev [12,13,14,15], in which the authors had obtained -as one consequence of a more general analysis -the following result:…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Eq. 1 and closely related results [5,6,7], along with experimental confirmations [8,9,10,11], have revealed that equilibrium free energy differences can be determined from distributions of nonequilibrium work values. The recent progress in this area has drawn attention to a set of earlier papers by Bochkov and Kuzovlev [12,13,14,15], in which the authors had obtained -as one consequence of a more general analysis -the following result:…”
Section: Introductionmentioning
confidence: 65%
“…For related discussions of this issue, particularly in the context of interpretation of experimental data, see Refs. [9,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…12 When the JE is defined in terms of the dissipative work W t d = W t ͑⌫͑0͒ , ͒ − ⌬F, relations ͑2͒ and ͑5͒ are extremely similar in form and they exhibit similar behaviors. Although both of these relations have been demonstrated in numerous systems, [17][18][19][20] the fact that they rely on determining the average of an exponential function using a finite set of data can cause significant problems in their application. …”
Section: − Ln Dv͑⌫͑0͒͒ Dv͑⌫͑t͒͒ ͑3͒mentioning
confidence: 99%
“…Besides providing new insight into the statistical mechanics of non-equilibrium processes, the Jarzynski identity has also been applied to extract equilibrium free energy differences from computer simulations 5,6,7,8,9 and experiments 10,11,12 . In particular, Liphardt et al 10 have determined the free energy required to unfold a single RNA chain from non-equilibrium work measurements and Douarche et al 11 have verified the Jarzynski equality for a mechanical oscillator that is driven out of equilibrium by an external force. Another experimental test of the Jarzynski equality was provided by Wang et al 12 who considered a colloidal particle pulled through liquid water by an optical trap 13 .…”
Section: Introductionmentioning
confidence: 99%